Anthropology of Communication and its Impact on Achieving Organizational Loyalty: An Exploratory Study in a Sample of Travel and Tourism Companies in Baghdad Governorate: Antropologi Komunikasi dan Dampaknya terhadap Pencapaian Loyalitas Organisasi: Studi Eksploratori pada Sampel Perusahaan Pariwisata dan Perjalanan di Provinsi Baghdad - Dr. Sheimaa Hameed Rasheed (Academia Open, 2026)
General Background: Communication plays a central role in shaping organizational relationships and cultural interactions within tourism institutions. In service-based sectors such as tourism, communication practices not only transmit information but also construct shared meanings that influence organizational commitment and employee behavior. Specific Background: Tourism organizations often face challenges such as high employee turnover and unstable workforce commitment, which are closely associated with the level of organizational loyalty among employees. Knowledge Gap: Despite the importance of communication processes, many tourism organizations still rely on traditional administrative approaches while paying limited attention to the anthropological dimensions of communication that shape social interaction and organizational culture. Aims: This study examines the role of communication anthropology in explaining organizational loyalty within tourism companies operating in Baghdad. Results: Based on a descriptive analytical approach and a field survey of 95 respondents, the findings indicate that communication anthropology dimensions, including cultural structure of meaning, interactive communicative acts, and reproduction of meaning, are statistically associated with higher levels of organizational loyalty among employees. Novelty: The study introduces communication anthropology as an analytical framework for understanding loyalty within tourism organizations by emphasizing cultural symbols, interaction patterns, and meaning construction. Implications: The findings suggest that tourism administrations should integrate communication-based cultural practices and strengthen semi-formal organizational interaction to support stronger employee commitment and organizational stability. Keywords: Communication Anthropology, Organizational Loyalty, Tourism Organizations, Cultural Communication, Employee Commitment Key Findings Highlights Cultural meaning structures shape employee attachment and belonging in tourism organizations. Communicative interaction patterns contribute to stronger workplace relationships. Meaning reproduction processes support stability within tourism work teams.